Role of labor migrants from Central Asia in the socio-economic development of Russia in the context of new global challenges - A. Kh. Rakhmonov (Управление)
The article studies history of migration among the countries of Central Asia and Russia, the factors and scale of emigration to Russia against the background of sanctions from the European Union and the USA, and migrants’ contribution to the economic and demographic development of the state. Migration processes from Central Asia to Russia have a long history dating back to Soviet times. After the collapse of the Soviet Union, migration took on unimaginable proportions and became one of the most important factors affecting economic and political life in both Central Asia and Russia. Labor migration began in the late 1990s and peaked in 2014. During their stay in Russia, migrants faced various crises. They have always played a significant role in the socio-economic development of the country. Although migration has always had both positive and negative consequences for the host countries, from an economic point of view it has rather a positive impact on the host countries’ economies. After February 2022 Western countries have imposed new economic and political sanctions against Russia, which have affected the situation and orientation of migrant workers from Central Asian countries. Some migrants have started to look for other emigration channels, while the majority are still focused on Russia. Compared with previous crises, the migrant workers’ role in Russia’s economic and demographic development has increased now against the background of new sanctions.